Nifedipine-sensitive noradrenergic vasoconstriction is enhanced in spontaneously hypertensive rats: the influence of chronic captopril treatment - Paulis, L'; Lísková, S; Pintérová, M; Dobesová, Z; Kunes, J; Zicha, J (Acta physiologica (Oxford, England), 2007)
AIM: The relationship between increased sympathetic tone and enhanced activity of L-type voltage-dependent Ca2+ channels (L-VDCC) in spontaneously hypertensive rats (SHR) was studied using in vivo and in vitro approaches. METHODS: The effects of acute L-VDCC blockade on sympathetic vasoconstriction or blood pressure (BP) and the contribution of calcium influx to norepinephrine (NE)-induced arterial contraction were investigated in 10-week-old SHR and in age-matched SHR made normotensive by chronic captopril treatment from weaning. RESULTS: Blood pressure fall occurring after acute ganglionic or L-VDCC blockade was enhanced in SHR. Ganglionic blockade eliminated strain differences in BP response to acute L-VDCC blockade and vice versa, suggesting that enhanced contribution of L-VDCC is responsible for augmented sympathetic vasoconstriction in SHR. Both phasic (dependent on internal calcium stores) and tonic (dependent on calcium influx) contractions to NE were augmented in SHR femoral arteries in vitro. Nifedipine attenuated only tonic contractions but to a larger extent in SHR than in WKY arteries. Nifedipine effect was greater after endothelium removal, which augmented tonic but not phasic contractions after NE. Chronic captopril treatment of SHR prevented hypertension development by suppression of their sympathetic vasoconstriction including its nifedipine-sensitive component, but failed to influence enhanced NE-induced arterial contractions or increased relaxation to nifedipine in vitro. CONCLUSION: The contribution of nifedipine-sensitive component to noradrenergic vasoconstriction is enhanced during excessive NE stimulation (increased sympathetic tone of SHR in vivo or supramaximal NE stimulation in vitro). It seems that captopril-induced reduction of central sympathetic tone is able to normalize augmented nifedipine-sensitive vasoconstriction in SHR.
Keywords: kaptopril; Calcium; Ion Channel Gating; nifedipin; Epinephrine; gating iontového kanálu; Hypertension; Nifedipine; Dose-Response Relationship, Drug; vápník; krysa rodu Rattus; blokátory kalciových kanálů; Adrenergic Agonists; Antihypertensive Agents; zvířata; vazokonstrikce; Captopril; Calcium Channel Blockers; agonisté adrenergních receptorů; Male; adrenalin; potkani inbrední SHR; hypertenze; Calcium Channels, L-Type; Rats; vápníkové kanály - typ L; vztah mezi dávkou a účinkem léčiva; Animals; antihypertenziva; mužské pohlaví; Vasoconstriction; Rats, Inbred SHR